Administración de recursos humanos y su aporte en el desarrollo organizacional - Paredes Funes, Karla Ximena (2019)
The present investigation of the case study shows the importance of the Human Resources Administration and its Contribution in Organizational Development so that employees can develop their skills and functions which perform their work in the Municipal GAD of the Urdaneta Canton to succeed both In the institution such as Canton Urdaneta to achieve the objectives and goals that aspire to the operation of the activities, we see that there is 67% who disagree that the role of human resources management is not important, which the 33% indicate that they agree that the role of human resources management is important for the proper functioning of activities and the development of their skills. But 100% disagree that good communication does not apply in the area of human resources, which we see that the human resources department is not functioning properly, because the people who do their job are not well trained, they evidenced that there was not the proper selection and evaluation of the human talent department at the time of hiring the staff to fill the vacancies of the assigned work position